Average Lumbar Hounsfield Units Predicts Osteoporosis-Related Complications Following Lumbar Spine Fusion. Issue 5 (June 2022) - St. Jeor, Jeffery D.; Jackson, Taylor J.; Xiong, Ashley E.; Freedman, Brett A.; Sebastian, Arjun S.; Currier, Bradford L.; Fogelson, Jeremy L.; Bydon, Mohamad; Nassr, Ahmad; Elder, Benjamin D.
Study Design: Retrospective Study. Objective: To compare methods of assessing pre-operative bone density to predict risk for osteoporosis related complications (ORC), defined as proximal junctional kyphosis, pseudarthrosis, accelerated adjacent segment disease, reoperation, compression fracture, and instrument failure following spine fusions. Methods: Chart review of primary posterior thoracolumbar or lumbar fusion patients during a 7 year period. Inclusion criteria: preoperative dual-energy x-ray absorptiometry (DXA) test within 1 year and lumbar CT scan within 6 months prior to surgery with minimum of 1 year follow-up. Exclusion criteria: <18 years at time of index procedure, infection, trauma, malignancy, skeletal dysplasia, neuromuscular disorders, or anterior-posterior procedures. Results: 140 patients were included. The average age was 67.9 years, 83 (59.3%) were female, and 45 (32%) had an ORC. There were no significant differences in patient characteristics between those with and without an ORC. Multilevel fusions were associated with ORCs (46.7% vs 26.3%, p = 0.02). Patients with ORCs had lower DXA t-scores (-1.62 vs -1.10, p = 0.003) and average Hounsfield units (HU) (112.1 vs 148.1, p ≤ 0.001). Multivariable binary logistic regression analysis showed lower average HU (Adj. OR 0.00 595% CI 0.0001-0.1713, p = 0.001) was an independent predictor of an ORC. The odds of an ORC increased by 1.7-fold for every 25 point decrease in average HU. Conclusions: The gold standard for assessing bone mineral density has been DXA t-scores, but the best predictor of ORC remains unclear. While both lower t-scores and average HU were associated with ORC, only HU was an independent predictor of ORC.